Auditoría de desempeño y la gestión administrativa de la Municipalidad Distrital de San Juan Bautista 2024 - Carihuasairo Jimenez, Gitzon Namber (2025)
This study investigates the relationship between performance auditing and the administrative management of the District Municipality of San Juan Bautista in 2024. The formulation of the problem focuses on the question: How does performance auditing relate to administrative management in this municipality? The objectives include identifying the relationship between performance auditing and its dimensions of effectiveness, efficiency, economy and quality in administrative management. A quantitative approach was employed, using a non-experimental cross-sectional design to collect data through surveys applied to civil servants in the municipality. The results reveal a significant positive relationship between performance audit and administrative management (p-value = 0.003), confirming the general hypothesis. Furthermore, it was identified that effectiveness, efficiency and economy of performance auditing are positively correlated with administrative management, with p-values of 0.004, 0.002 and 0.004, respectively. The findings highlight the importance of implementing performance audits to improve administrative management, optimise the use of public resources and ensure greater transparency and accountability in public administration. The research proposes recommendations for strengthening staff training and adapting policies that foster continuous improvement in public management.